Returning to Activity After Anterior Cruciate Ligament Revision Surgery: An Analysis of the Multicenter Anterior Cruciate Ligament Revision Study (MARS) Cohort at 2 Years Postoperative. Issue 7 (June 2022) - ; Bigouette, John P.; Owen, Erin C.; Lantz, Brett (Brick) A.; Hoellrich, Rudolf G.; Wright, Rick W.; Huston, Laura J.; Haas, Amanda K.; Allen, Christina R.; Cooper, Daniel E.; DeBerardino, Thomas M.; Dunn, Warren R.; et al.
Background: Patients with anterior cruciate ligament (ACL) revision report lower outcome scores on validated knee questionnaires postoperatively compared to cohorts with primary ACL reconstruction. In a previously active population, it is unclear if patient-reported outcomes (PROs) are associated with a return to activity (RTA) or vary by sports participation level (higher level vs. recreational athletes). Hypotheses: Individual RTA would be associated with improved outcomes (ie, decreased knee symptoms, pain, function) as measured using validated PROs. Recreational participants would report lower PROs compared with higher level athletes and be less likely to RTA. Study Design: Cohort study; Level of evidence, 2. Methods: There were 862 patients who underwent a revision ACL reconstruction (rACLR) and self-reported physical activity at any level preoperatively. Those who did not RTA reported no activity 2 years after revision. Baseline data included patient characteristics, surgical history and characteristics, and PROs: International Knee Documentation Committee questionnaire, Marx Activity Rating Scale, Knee injury and Osteoarthritis Outcome Score, and the Western Ontario and McMaster Universities Osteoarthritis Index. A binary indicator was used to identify patients with same/better PROs versus worse outcomes compared with baseline, quantifying the magnitude of change in each direction, respectively. Multivariable regression models were used to evaluate risk factors for not returning to activity, the association of 2-year PROs after rACLR surgery by RTA status, and whether each PRO and RTA status differed by participation level. Results: At 2 years postoperatively, approximately 15% did not RTA, with current smokers (adjusted odds ratio [aOR] = 3.3; P = .001), female patients (aOR = 2.9; P < .001), recreational participants (aOR = 2.0; P = .016), and those with a previous medial meniscal excision (aOR = 1.9; P = .013) having higher odds of not returning. In multivariate models, not returning to activity was significantly associated with having worse PROs at 2 years; however, no clinically meaningful differences in PROs at 2 years were seen between participation levels. Conclusion: Recreational-level participants were twice as likely to not RTA compared with those participating at higher levels. Within a previously active cohort, no RTA was a significant predictor of lower PROs after rACLR. However, among patients who did RTA after rACLR, approximately 20% reported lower outcome scores. Most patients with rACLR who were active at baseline improved over time; however, patients who reported worse outcomes at 2 years had a clinically meaningful decline across all PROs.